The Practicality of Popular Scientific Book of Fungi in Tabanio Beach Forest as Enrichment for Botani Tumbuhan Rendah Course - Putri Pratami Rahmiati; Yudi Firmanul Arifin; Atiek Winarti (BIO-INOVED : Jurnal Biologi-Inovasi Pendidikan, 2021)
Learning resources can be developed by utilizing the surrounding environment or based on local potential. Individual intelligence will grow and develop through a process of interaction with their environment, so it is necessary to use the environment in contextual learning. One of the sources of learning based on local potential that can be developed is popular scientific books. The development of learning resources in the form of popular scientific books in this study aims to overcome the problem of limited learning resources in low plant botanical subjects, especially on the topic of fungi with macroscopic materials and examples of fungi from the environment. This development research aims to test the practicality of a popular scientific book entitled "Forest Fungi Tabanio Beach". This development method uses Tessmer's formative evaluation. The practicality of popular scientific books was carried out by 3 students as small group test subjects to obtain expected practicality data and 17 students as field test subjects to obtain actual practicality data using student response questionnaires. In addition, data on the implementation of popular scientific books which were assessed by 3 observers were also obtained. The results showed that the developed popular scientific books were practical to be used as enrichment for Low Plant Botany courses.Abstrak Sumber belajar dapat dikembangkan dengan memanfaatkan lingkungan sekitar atau berbasis potensi lokal. Intelegensi individu akan tumbuh dan berkembang melalui proses interaksi dengan lingkungannya, sehingga perlu adanya pemanfaatan lingkungan dalam pembelajaran kontekstual. Sumber belajar berbasis potensi lokal yang dapat dikembangkan salah satunya yaitu buku ilmiah populer. Pengembangan sumber belajar berbentuk buku ilmiah populer dalam penelitian ini dilakukan untuk mengatasi masalah keterbatasan sumber belajar pada mata kuliah botani tumbuhan rendah khususnya pada topik jamur dengan materi dan contoh-contoh jamur makroskopis dari lingkungan. Penelitian pengembangan ini bertujuan untuk menguji kepraktisan buku ilmiah populer yang berjudul "Jamur Hutan Pantai Tabanio". Metode pengembangan ini menggunakan evaluasi formatif dari Tessmer. Kepraktisan buku ilmiah populer dilakukan oleh 3 orang mahasiswa sebagai subjek uji small group untuk memperoleh data kepraktisan harapan dan 17 orang mahasiswa sebagai subjek uji field test untuk memperoleh data kepraktisan aktual dengan menggunakan angket respon mahasiswa. Selain itu juga diperoleh data keterlaksanaan buku ilmiah populer yang dinilai oleh 3 observer. Hasil penelitian menunjukkan buku ilmiah populer yang dikembangkan praktis digunakan sebagai pengayaan mata kuliah Botani Tumbuhan Rendah.